The Canadian State and Native Migrant Labour in Southern Alberta's Sugar Beet Industry - Laliberte, Ronald F. (University of Saskatchewan, 1994)
Recent studies of labour have clearly established that the capitalist state is very involved in the recruitment, relocation and retention of migrant labour forces. Most of the literature tends to analyze migrant labour within the broader social, political and economic context of expanding capitalism. Consequently, studies tend to focus on how the use of migrant labour is profitable to capitalism because it is cheap and easy to exploit. Such studies, however, neglect the ways in which the state actually intervenes in the labour market in order to facilitate the flow of migrant workers to places of employment. Therefore, this thesis explores the relationship between the migration of labour, the state and the reserve army of labour through an analysis of the Native migrant work force in the sugar beet industry in southern Alberta.

Native Migrant Labour in the Southern Alberta Sugar-beet Industry: Coercion and Paternalism in the Recruitment of Labour* - Laliberte, Ronald F.; Satzewich, Vic (Canadian Review of Sociology/Revue canadienne de sociologie, 1999)
Research has begun to increasingly document Native peoples' participation in wage employment in Canada. Despite an acknowledgement of native participation in wage labour, little is known of the role of the state in mobilizing Native workers for Canadian industry. Using the case of Native migration to the southern Alberta sugar-beet industry in the 1950s and 1960s, this paper analyzes the role of the state in the mobilization of the native workers for employment. We show that the various levels of the state, acting through federal/provincial manpower committees and the Indian Affairs Branch of the federal government, used a variety of paternalistic and coercive measures to help farmers in southern Alberta recruit and retain Native workers. One of the main measures used by the federal and provincial governments to coerce Native people into migration was to cut off social assistance benefits to those Native people deemed to be employable.